Hambatan Penerapan Kebijakan Energi Terbarukan di Indonesia - Sahid Yudhakusuma Kalpikajati; Sapto Hermawan (Batulis Civil Law Review, 2022)
Indonesia is a country with a lot of undeniable wealth. Besides the wealth of social and culture, Indonesia also gifted with very abundant natural resources. Which also include those potential renewable energy sources which can be found in every corner of the country. With this kind of wealth, Indonesia should be able to have resilience, independence, and energy sovereignty that sufficient the needs of its people. Unfortunately, currently Indonesia still relies on non-renewable energy sources to support the development and economic activities of its people. By using the literature method through primary and secondary data sources, this study aims to identify any obstacles in implementing renewable energy policies in Indonesia. The results of this research is that there are two main obstacles on implementing renewable energy sources; both of them are juridical obstacle and social obstacle.